A Case of Concurrent COPD Exacerbation, Osteoporosis, and Fracture: Unveiling the Interplay - Fadhilla Annisa Efendi; Masrul Basyar; Deddy Herman; Yessy Susanty Sabri (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Chronic obstructive pulmonary disease (COPD) is a prevalent respiratory condition with systemic effects, including an increased risk of osteoporosis and fractures. This case report presents a patient with acute COPD exacerbation, osteoporosis, and vertebral fractures, highlighting the complex interplay between these conditions. Case presentation: A 68-year-old male patient presented with acute exacerbation of COPD. He had a history of smoking, hypertension, and a previous diagnosis of pulmonary tuberculosis. Clinical examination revealed signs of respiratory distress, and imaging confirmed emphysema, pneumonia, osteoporosis, and vertebral fractures. The patient received treatment for COPD exacerbation and osteoporosis, showing improvement in respiratory symptoms and pain. Conclusion: This case underscores the importance of recognizing the association between COPD, osteoporosis, and fractures. Early diagnosis and appropriate management of these co-morbidities are crucial for improving patient outcomes and quality of life.